Can information from publicly available sources reveal manipulation of financial statements? - Eva Hýblová; Alena Kolčavová; Tomáš Urbánek; Zora Petráková (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
Financial reporting is a source of information used as a basis for economic decisions. It is a basis for the calculation of financial indicators that serve to evaluate the financial health of a company. Statements that are accurate and provide trustworthy information are a prerequisite for an enhancement of company competitiveness on national and global markets. Research into and studies on the accuracy of the information contained in statements show that statement creators use manipulation to improve accounting entities' image. The aim of this paper is to verify whether ordinary users of financial statements can rely on the veracity of the information contained in the financial statements published in the usual way in available sources. The research subject was financial statements of entities listed in the TOP Czech and TOP Slovak ranking within the revenue category. We investigated whether statements show an indication of accounting data manipulation using the CFEBT (cash flow earning before tax) method and a method aimed at verifying the linear dependence between earning before tax (EBT) and cash flow (CF). The empirical results yielded interesting findings. They showed that the disputable item is the results of accounting estimates, which are often influenced by subjective decisions made by the financial statements creators.
Keywords: M40; M41; 330; Accounting; Financial reporting; Creative accounting; Model comparison; CFEBT